Tracking Delays in Neurosurgical Care during the COVID-19 Pandemic. (16th November 2020) - Patel, Pious D; Kelly, Katherine A; Reynolds, Rebecca; Turer, Robert; Salwi, Sanjana; Rosenbloom, S. Trent; Bonfield, Christopher M.,; Naftel, Robert P.,
Abstract: INTRODUCTION: The COVID-19 pandemic has substantially disrupted inpatient and outpatient neurosurgical care. METHODS: Patients who underwent a neurosurgical operation, inpatient consult, or outpatient appointment at Vanderbilt University Medical Center between March 23, 2019 and April 20, 2020 were identified. The March 23, 2020 Tennessee gubernatorial executive order was used to distinguish pre- and post-COVID cases. RESULTS: The total number of pre- and post-COVID cases was 4, 152 and 195, respectively. Overall, a 45% reduction in median weekly operative case volume was demonstrated (82/week to 45/week; P = . 001) after March 23. There was an observed downtrend in case volume in the weeks leading up to March 23. There was a 47% reduction for adult procedures (68/week to 36/week; P = . 001) and 29% reduction for pediatrics (14/week to 10/week; P = . 017). Among adult procedures, the most significant decreases were seen for spine surgeries ( P = . 008) and endovascular procedures ( P = . 036). Total weekly inpatient consults to adult neurosurgery decreased by 30% (97/week to 68/week; P < . 001) with no significant change to pediatric consults. Adult and pediatric outpatient clinic visits decreased by 28% (552/week to 400/week; P = . 021), with a 54% decrease for in-person encounters (551/week to 254/week; P = . 001). Weekly Telehealth encounters increased from 0/week to 130/week. CONCLUSION: There was a significant reduction in pediatric and adult neurosurgical procedures, clinic visits, and adult inpatient consults during COVID-19. Telemedicine was increasingly used for assessment. Identifying neurosurgical procedures most impacted by COVID-19 delays may aid in the development of effective triage strategies for elective surgeries as they are reinstated.